Frigram: a French Interaction Grammar - Perrier, Guy; Guillaume, Bruno (Journal of Language Modelling, 2015)
We present Frigram, a French grammar with a large coverage, written in the formalism of Interaction Grammars. The originality of the formalism lies in its system of polarities which expresses the resource sensitivity of natural languages and which is used to guide syntactic composition. We present the principles underlying grammar design, highlight its modular architecture and show that the lexicon used is independent of the grammar formalism. We also introduce the “companion property”, and show that it helps to enforce grammar consistency.